2016
DOI: 10.3390/molecules21101286
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effect of Quercetin in Xenograft Models with EBV-Associated Human Gastric Carcinoma

Abstract: Licorice extracts have been widely used in herbal and folk medications. Glycyrrhiza contains diverse range of biological compounds including triterpenes (glycyrrhizin, glycyrrhizic acid) and flavonoids (quercetin, liquiritin, liquiritigenin, glabridin, licoricidin, isoliquiritigenin). The flavonoids in licorice are known to have strong anti-cancer activities. Quercetin, the most abundant flavonoid, has been shown to have anti-ulcer, anti-cancer, antioxidant, and anti-inflammatory properties. Latent Epstein-Bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 37 publications
0
21
1
Order By: Relevance
“…In human pancreatic cancer cell lines CFPAC‐1 and SNU‐213, quercetin‐3‐O‐glucoside suppresses the migratory activity induced by transforming growth factor‐beta (TGF‐β) and vascular endothelial growth factor A even at relatively low dosages in CFPAC‐1, but not in bFGF‐activated SNU‐213 cells. In addition, co‐treatment with low dose of gemcitabine and quercetin‐3‐O‐glucoside exhibited synergistic inhibition effects on the infiltrate activity induced by bFGF in CFPAC‐1 and SNU‐213 cells (J. Lee, Lee, Kim, & Kim, ; H. H. Lee, Lee, Shin, et al, ).…”
Section: Anticancer Perspectives Of Quercetinmentioning
confidence: 99%
See 1 more Smart Citation
“…In human pancreatic cancer cell lines CFPAC‐1 and SNU‐213, quercetin‐3‐O‐glucoside suppresses the migratory activity induced by transforming growth factor‐beta (TGF‐β) and vascular endothelial growth factor A even at relatively low dosages in CFPAC‐1, but not in bFGF‐activated SNU‐213 cells. In addition, co‐treatment with low dose of gemcitabine and quercetin‐3‐O‐glucoside exhibited synergistic inhibition effects on the infiltrate activity induced by bFGF in CFPAC‐1 and SNU‐213 cells (J. Lee, Lee, Kim, & Kim, ; H. H. Lee, Lee, Shin, et al, ).…”
Section: Anticancer Perspectives Of Quercetinmentioning
confidence: 99%
“…Quercetin viably prompted p53‐dependent apoptosis than isoliquiritigenin in EBV(+) human gastric carcinoma, and this enlistment was related with expanded expressions of the separated types of caspase‐3, ‐9, and Parp. In EBV(−) human gastric carcinoma (MKN74), quercetin instigated the expressions of p53, Bax, and Puma and the separated types of caspase‐3 and ‐9 and Parp at comparative levels (J. Lee, Lee, Kim, et al, ; H. H. Lee, Lee, Shin, et al, ). In gastric cancer stem cells, quercetin induced cell apoptosis in a mitochondrial‐dependent approach through (a) lessening in mitochondrial membrane potential, (b) enhancement of caspase‐3 and ‐9, (c) down‐regulation of Bcl‐2, and (d) up‐regulation of Bax and cytochrome c. It, likewise, caused mitochondrial apoptotic‐dependent growth inhibition by diminishing the PI3K‐Akt signaling and suppressed the overexpression of Bcl‐2 and kept the reduction in mitochondrial film potential.…”
Section: Anticancer Perspectives Of Quercetinmentioning
confidence: 99%
“…Liquiritin is one of active ingredients extracted from the root of Glycyrrhiza uralensis. Emerging studies have shown that liquiritin has multiple beneficial effects, such as anti-oxidation, anti-allergy, immunity-enhancing, anti-thrombosis and neuroprotection effects [23,24]. More importantly, liquiritin has powerful inhibitory effects on the development of various cancers, such as gastric cancer, cervical cancer and lung cancer [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Liquiritin (Fig. 1A), an active component of Glycyrrhiza Radix, possesses multiple pharmacological activities including antiinflammation, neuroprotection, anti-cancer activities [23,24]. For example, liquiritin induces apoptosis and autophagy in cisplatin (DDP)-resistant gastric cancer [25].…”
mentioning
confidence: 99%
“…After 14 days, both groups were subdivided into 2 subgroups ( n = 6, respectively) and orally administrated drinking water and adenosine (30 mg/kg) for 17 days. Administration amounts of adenosine were determined based on our previous studies; 30 mg/kg for quercetin and isoliquiritigenin [44]. Tumors were identified and measured every other day using a standard caliper; tumor size was calculated using [tumor length (mm) × tumor width (mm) 2 ]/2 as previously described [21].…”
Section: Methodsmentioning
confidence: 99%